Arterial Stiffness Can Be Modulated by Pressure‐Independent Mechanisms in Hypertension. Issue 15 (6th August 2019) - Faconti, Luca; Farukh, Bushra; McNally, Ryan; Webb, Andrew; Chowienczyk, Phil
Abstract : Background: Effects of short‐term interventions on large‐artery stiffness assessed by pulse wave velocity (PWV) have mainly been explained by concomitant changes in blood pressure (BP). However, lower body negative pressure, which increases sympathetic activity and has other hemodynamic effects, has a specific effect on PWV in healthy volunteers. Methods and Results: We examined effects of lower‐limb venous occlusion (LVO), a similar intervention to lower‐body negative pressure that reduces BP but increases sympathetic activity and device‐guided breathing (DGB), which reduces both BP and sympathetic activity, on PWV in patients with essential hypertension (n=70 after LVO, n=45 after DGB and LVO in random order). The short‐acting calcium channel antagonist nifedipine was used as a control for changes in BP. LVO produced a small but significant reduction in mean arterial pressure of 1.8 (95% CI 0.3–3.4) mm Hg. Despite this, aortic and carotid‐femoral PWV increased during LVO by 0.8 (0.2–1.4) m/s and 0.7 (0.3–1.05) m/s, respectively. DGB reduced PWV by 1.2 (0.9–1.4) m/s, to a greater extent than did nifedipine 10 mg (reduction of 0.7 [0.1–1.3] m/s, P <0.05 compared with reduction during DGB). This occurred despite a greater decrease in BP with nifedipine compared with DGB. Conclusions: Arterial stiffness can be modulated independently of BP over the short term. The mechanism could involve alterations in sympathetic activity or other as yet uncharacterized effects of LVO and DGB.